CRUELTY A GROUND FOR DISSOLUTION OF MARRIAGE: A COMPARATIVE STUDY OF SHARIAH LAW AND COURT’S PRACTICES (Zia e Tahqeeq, 2025)
Islām being a religion of peace directs the Muslims in all the sphere of life by enjoining kindness and warns any hasty judgment. In Family matters dissolution of marriage is allowed when the differences and aversion arises between the spouses and the relation becomes unbearable and unendurable. Cruelty no matter mentally or physically provides a ground of separation to a Muslim wife. In Pakistan, the case law shows that in court a wife is demanded to provide satisfactory evidence to prove the claim of cruelty, failure of which the suit for dissolution of marriage will be set aside. This has caused difficulty to the wife, as it is practically hard to fulfill this requirement. The research also argues that the view prescribed in the Qurʼānic verses “retain them honorable or set them free kindly” (Al-Baqarah-231) is a general and absolute principle, within that framework and rule the rights of woman can be read and should be observed. This research answered several crucial questions such as what is the concept of cruelty in Islamic law and what is the court’s ruling to address it? Does a Muslim woman is given a right of dissolution on ground of Cruelty or can a court grant such dissolution on the request of wife? The descriptive as well as analytical research methods have been utilized to explore different areas and to analyze the Islamic law and the legal rulings in Pakistan regarding the cruelty. The methodology of case study is applied and 15 decided cases have been selected to analyze the cruelty as a ground of separation.